Oral Signs and HLA-DQB1*02 Haplotypes in the Celiac Paediatric Patient: A Preliminary Study. (3rd October 2013) - Erriu, M.; Abbate, G. M.; Pili, F. M. G.; Novara, F.; Orrù, G.; Montaldo, C.; Piras, V.; Levrini, L.
Abstract : Celiac disease (CD) diagnosis can be extremely challenging in the case of atypical patterns. In this context, oral signs seem to play a decisive role in arousing suspicion of these forms of the disease. At the same time, the different expressions of the HLA-DQB1*02 allele apparently seem to facilitate the interpretation of signs and highlighted symptoms. The aim of this work was to verify whether it is possible to identify a correlation between the development of oral signs and different DQ2 haplotypes in celiac pediatric patients. 44 celiac patients with a medium age of 9.9 were studied. Oral examinations were performed in order to identify recurrent aphthous stomatitis (RAS) and dental enamel defects (DED). The diagnosis of DED resulted as being related to allele expression (P value = 0.042) while it was impossible to find a similar correlation with RAS. When both oral signs were considered, there was an increase in correlation with HLA-DQB1*02 expression (P value = 0.018). The obtained results identified both the fundamental role that dentists can play in early diagnosis of CD, as well as the possible role of HLA haplotype analysis in arousing suspicion of atypical forms of the disease.